2016
DOI: 10.1007/s00394-016-1319-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of urinary metabolites with potential blood pressure-lowering effects in lentil-fed spontaneously hypertensive rats

Abstract: Consumption of lentils increases the availability of arginine and several related compounds that could potentially elevate production of NO and contribute to the blood pressure-lowering effects of lentil-rich diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Cytidine (C 9 H 13 N 3 O 5 ) and norvaline (C 5 H 11 NO 2 ) were used as internal standards (IS) to validate the extraction and MS methods used in this study. These compounds were chosen because their efficacy has been previously tested in our laboratory when added as IS to either biological samples or food samples . Cytidine gave satisfactory results in our previous HPLC analysis of nucleotides, nucleosides and bases in chicken breast and bison meats coupled with UV detection and was selected to be tested in this LC/QTOF‐MS application.…”
Section: Resultsmentioning
confidence: 99%
“…Cytidine (C 9 H 13 N 3 O 5 ) and norvaline (C 5 H 11 NO 2 ) were used as internal standards (IS) to validate the extraction and MS methods used in this study. These compounds were chosen because their efficacy has been previously tested in our laboratory when added as IS to either biological samples or food samples . Cytidine gave satisfactory results in our previous HPLC analysis of nucleotides, nucleosides and bases in chicken breast and bison meats coupled with UV detection and was selected to be tested in this LC/QTOF‐MS application.…”
Section: Resultsmentioning
confidence: 99%
“…Maximum excretions of these compounds were observed 4 and 6 h, respectively, after intake of lentils, although differences were observed from the first few hours until 48 h post-consumption (Table 1). Hydroxyarginine is a free nonprotein amino acid particular to lentils, [9] and oxoarginine is a metabolite of the arginine pathway recently associated with lentil consumption. [9] Therefore, they are interesting indicators of lentil intake.…”
Section: Bfi For Lentilsmentioning
confidence: 99%
“…Hydroxyarginine is a free nonprotein amino acid particular to lentils, [9] and oxoarginine is a metabolite of the arginine pathway recently associated with lentil consumption. [9] Therefore, they are interesting indicators of lentil intake. Additionally, it has been suggested that they could contribute to the blood pressure-lowering effects associated with the consumption of lentils through an increase in the production of nitric oxide.…”
Section: Bfi For Lentilsmentioning
confidence: 99%
See 2 more Smart Citations